Extracellular matrix-based hybrid ink for 3D printing and its manufacturing method
A biomaterial-based hybrid ink, chemically cross-linked with extracellular matrix and methacrylated hyaluronic acid, addresses the challenges of controlled angiogenic factor delivery, promoting angiogenesis through spatial and temporal release of VEGF and HGF, improving treatment efficacy for cerebral ischemia.
Patent Information
- Application Number
- JP2024537132
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-20
- Filing Date
- 2022-03-14
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-03-14
AI Technical Summary
Existing methods for administering angiogenic factors to treat cerebral ischemia, such as intravenous injection, require high doses and repeated deliveries, leading to reduced efficacy and serious side effects, and there is a need for a localized, controlled drug delivery system that can spatially and temporally release these factors to promote angiogenesis.
A biomaterial-based hybrid ink is developed through chemical cross-linking of extracellular matrix and methacrylated hyaluronic acid, incorporating angiogenic growth factors, which is 3D printed to create a patch that sequentially releases VEGF and HGF, promoting angiogenesis by spatial and temporal compartmentalization of these factors.
The patch effectively promotes angiogenesis by controlled release of VEGF and HGF, enhancing blood vessel formation and reducing side effects, as demonstrated by in vitro and in vivo experiments.
Smart Images

Figure 2025500950000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an extracellular matrix-based hybrid ink, and more particularly to an extracellular matrix-based hybrid ink for 3D printing, in which the crosslinking density is adjusted by chemical bonds between internal components, and the ink has mechanical properties suitable for 3D printing and the drug release rate can be controlled, and a method for producing the ink is also related to the present invention. [Background technology]
[0002] Cerebral ischemia occurs when insufficient blood flow to the brain causes cerebral hypoxia and death of brain tissue. Due to its severity, cerebral ischemia is known to be one of the most frequent causes of death worldwide. To treat ischemic brain tissue, it is essential to maintain the patency of newly formed blood vessels through a continuous supply of angiogenic growth factors and induce angiogenesis, in which capillaries extend from existing blood vessels to generate new blood vessels. The angiogenic process is a complex, multi-step process that involves a variety of angiogenic growth factors required at the right time, and serves to continuously supply oxygen and nutrients required for cell penetration and metabolism. Therapeutic methods that deliver angiogenic factors to promote angiogenesis have emerged as a promising strategy for the treatment of severe ischemic diseases.
[0003] Angiogenic factors that promote the early and mature steps of therapeutic angiogenesis are well known. In addition, the administration of angiogenic factors acting at each step together is also recognized as a useful method for promoting vascular regeneration. In particular, vascular endothelial growth factor (VEGF) is one of the important factors that promote the early step of angiogenesis, inducing the proliferation of endothelial cells to generate immature blood vessels. However, concerns have been raised about the clinical use of VEGF due to its side effects, such as proinflammatory responses such as increased vascular permeability. Hepatocyte growth factor (HGF) is another important angiogenic factor that promotes the mature step of angiogenesis, and when applied together with VEGF, it causes synergistic effects, such as reducing the side effects of VEGF and promoting the growth of vascular endothelial cells. Thus, the sequential release process of these two angiogenic factors induces a stronger angiogenic response and prevents vascular regression and blood leakage. Therefore, the continuous administration of such multiple angiogenic factors that mimic the angiogenic process is essential for the angiogenesis process of ischemic sites.
[0004] However, traditional growth factor administration methods such as intravenous injection often require high doses or repeated delivery to stimulate a therapeutic effect, resulting in reduced efficacy and serious side effects. To solve this, such factors must be administered at a physiologically appropriate time (time regulation) and in a targeted manner to the appropriate site (site-specific). Therefore, it is necessary to develop a soft and flexible hydrogel patch-type drug delivery system that can regulate the release profile of angiogenic factors and can be applied locally to soft brain regions. 3D printing technology can be used to fabricate such a patch. Through the use of 3D printing technology and various types of biomaterials, a controllable and user-definable patch-type delivery system can be freely fabricated. The release profile of angiogenic factors can be regulated by adjusting 3D printing variables (e.g., system dimensions and design) or through the adjustment of material properties (e.g., synthetic and naturally derived biomaterials, crosslinking density and concentration). In the case of biomaterials, extracellular matrix (ECM)-based hydrogels with tissue properties and printability have been proposed as a viable option.
[0005] Recently, studies have reported the possibility of using vascular tissue-derived decellularized extracellular matrix (VdECM) as a material for drug delivery. However, VdECM alone has the disadvantage that it is difficult to use as a printable biomaterial ink due to its poor printability (G. Gao, JY Park, BSKim, J. Jang, DW Cho, Advanced healthcare materials 2018, 7, 1801102.).
[0006] In relation to extracellular matrix-based bioinks for 3D printing, Korean Patent Publication No. 10-1954953 describes a process for producing a temperature-sensitive hydrogel containing cell culture medium, hyaluronic acid, gelatin, fibrinogen, and glycerol, and a process for producing a decellularized extracellular matrix by decellularizing tissue extracted from the body and powdering it to a particle size of 0.05 to 100 μm. (c) preparing a decellularized extracellular matrix (dECM) powder from the temperature-sensitive hydrogel obtained in step (a) at 30 to 40°C; (d) preparing a decellularized extracellular matrix-based bioink by mixing the decellularized extracellular matrix powder obtained in step (b) with the temperature-sensitive hydrogel in the sol state of step (c) through stirring; and (e) mixing the decellularized extracellular matrix-based bioink prepared in step (d) with cells derived from a target tissue and pouring the mixture into a cartridge for a 3D bioprinter. (f) maintaining the 3D bioprinter cartridge of step (e) at 3 to 6°C for 8 to 15 minutes to induce temperature-induced gelation of the cells in the cartridge and the decellularized extracellular matrix-based bioink; (g) 3D bioprinting a target artificial tissue using the 3D bioprinter cartridge containing the cells and the decellularized extracellular matrix-based bioink in which gelation has been induced in step (f); and (h) treating the target artificial tissue 3D bioprinted in step (g) with a thrombin solution and maintaining it at 20 to 25°C for 25 to 35 minutes to induce gelation by an enzymatic polymerization reaction of thrombin and fibrinogen. In addition, Korean Patent Publication No. 10-2302770 discloses a bioink composition for 3D printing that contains finely divided human tissue-derived components and a biocompatible polymer, and the finely divided human tissue-derived components have a particle size of 10 to 1000 um. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been derived against the background of the prior art, and an object of the present invention is to provide an extracellular matrix-based hybrid ink for 3D printing, which has mechanical properties suitable for 3D printing and can control the drug release rate, and a method for producing the same.
[0008] It is also an object of the present invention to provide a biomaterial-based drug delivery patch and a method for making the same.
[0009] It is also an object of the present invention to provide a biomaterial-based patch that can be used to promote angiogenesis or treat diseases associated with angiogenesis. [Means for solving the problem]
[0010] The inventors of the present invention have developed an extracellular matrix-based hybrid ink that has mechanical properties suitable for 3D printing and can control the drug release rate by chemically bonding the amine group of the extracellular matrix and the methacrylate group of methacrylated hyaluronic acid through an aza-Michael addition reaction. In addition, the inventors of the present invention added an angiogenic growth factor capable of promoting cerebral angiogenesis to the extracellular matrix-based hybrid ink and then 3D printed it to fabricate a hydrogel patch in which the angiogenic growth factor is spatially compartmentalized and the angiogenic growth factor is sequentially released. The inventors of the present invention implanted a patch in which two types of angiogenic growth factors were spatially and temporally compartmentalized into the brain and monitored it through a photoacoustic microscope, confirming that angiogenesis was effectively promoted.
[0011] In order to achieve the above-mentioned object, one example of the present invention provides an extracellular matrix-based hybrid ink for 3D printing, which comprises an extracellular matrix having an amine group and a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, characterized in that the extracellular matrix and the modified hyaluronic acid are in a crosslinked state due to chemical bonds formed between at least a portion of the amine groups present in the extracellular matrix and the ethylenically unsaturated bond functional group present in the modified hyaluronic acid.
[0012] To achieve the above object, one example of the present invention provides a method for producing an extracellular matrix-based hybrid ink for 3D printing, comprising the steps of: preparing an extracellular matrix solution having a pH of 6.5 to 7.5; adding modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein to the extracellular matrix solution, mixing the mixture uniformly, and then conducting an aza-Michael addition reaction to obtain an ink composition in which the extracellular matrix and the modified hyaluronic acid are crosslinked.
[0013] In order to achieve the above-mentioned object, one example of the present invention provides a biomaterial-based drug delivery patch, which is a patch having a multilayer structure including an inner core layer and an outer layer surrounding the inner core layer, wherein the inner core layer and the outer layer are made of an extracellular matrix-based hybrid ink, the hybrid ink containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a growth factor, the extracellular matrix and the modified biopolymer constituting the hybrid ink are present in a chemically crosslinked state, and the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer have different chemical crosslinking densities and contain different growth factors.
[0014] To achieve the above object, one example of the present invention provides a method for manufacturing a biomaterial-based drug delivery patch, the method comprising the steps of: preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state; preparing a second hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor different from the first growth factor, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state, the second hybrid ink having a different chemical crosslinking density from the first hybrid ink; 3D printing the second hybrid ink to form an inner core layer; and 3D printing the first hybrid ink to form an outer layer surrounding the inner core layer, thereby obtaining a multi-layer structure.
[0015] In order to achieve the above object, one example of the present invention provides a biomaterial-based patch for promoting angiogenesis, the patch having a multi-layer structure including an inner core layer and an outer layer surrounding the inner core layer, the outer layer being made of a first hybrid ink based on an extracellular matrix, and the inner core layer being made of a second hybrid ink based on an extracellular matrix, the first hybrid ink including an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor promoting an early stage of angiogenesis, the second hybrid ink including an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor promoting a mature stage of angiogenesis, the extracellular matrix and the modified biopolymer constituting the first hybrid ink and the second hybrid ink being in a chemically crosslinked state, and the second hybrid ink having a greater chemical crosslinking density than the first hybrid ink.
[0016] To achieve the above object, one example of the present invention provides a method for manufacturing a biomaterial-based patch for promoting angiogenesis, the method comprising the steps of: preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor that promotes an early stage of angiogenesis, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state; preparing a second hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor that promotes a mature stage of angiogenesis, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state, and having a higher chemical crosslinking density than the first hybrid ink; 3D printing the second hybrid ink to form an inner core layer; and 3D printing the first hybrid ink to form an outer layer surrounding the inner core layer, thereby obtaining a multi-layer structure.
[0017] The biomaterial-based pro-angiogenic patch can also be used to treat diseases associated with angiogenesis. Effect of the Invention
[0018] The hybrid ink according to one embodiment of the present invention has mechanical properties suitable for 3D printing due to chemical crosslinking between the components, the extracellular matrix and denatured hyaluronic acid, and the drug release rate can be controlled by adjusting the chemical crosslinking density. A multi-layered patch in which different growth factors are spatially and temporally compartmentalized and fabricated by 3D printing the hybrid ink according to one embodiment of the present invention can be used as a drug delivery system, to promote angiogenesis, or to treat diseases related to angiogenesis, since different growth factors are released sequentially. [Brief description of the drawings]
[0019] [Figure 1]This study outlines the process for fabricating hybrid ink (HAVEM ink) from vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) using dual crosslinking mechanisms, such as chemical crosslinking and thermal crosslinking. [Diagram 2] In this study, cerebrovascularization-inducing growth factors VEGF and HGF were added to hybrid inks with different cross-linking densities, and a schematic process for manufacturing a spatiotemporal compartmentalized cerebral angiogenesis inducing (SCAI) patch using a 3D printing process was shown, along with a schematic process for the sequential release of VEGF and HGF in the SCAI patch. [Diagram 3] This is a schematic diagram of the process of preparing HAVEM ink from vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) through aza-Michael addition reaction. [Figure 4] These are spectra measured by nuclear magnetic resonance (NMR) of VdECM ink (4V0H), HAMA, and HAVEM ink (4V0.5H) to prove the occurrence of cross-linking between vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA). [Diagram 5] The above photograph shows the sol state images of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) due to differences in chemical cross-linking density, and the graph below Figure 5 shows the viscosity of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) measured at printing conditions of 4°C and various shear rates. [Figure 6]This shows the change in elastic modulus of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) due to a temperature change from 4°C to 37°C. [Figure 7] This shows the storage modulus and loss modulus of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) depending on the change in vibration frequency at a temperature of 37°C. [Figure 8] The release profiles of HGF encapsulated in HAVEM ink (4V0.5H) and HAVEM ink (4V1H) were measured for 7 days. [Figure 9] This study outlines the process of fabricating a SCAI patch using 3D printing technology. [Figure 10] The results show that the angiogenic effects of various angiogenic factors were measured by a tube formation assay. [Figure 11] The cross-sectional structure of the SCAI patch produced in this study and images of each cross section taken with a confocal microscope (scale bars: 200 μm). [Figure 12] The design structure of SCAI patches fabricated with various combinations of HAVEM inks and images of each patch at the printing, gelling and vitrification steps. [Figure 13] The tensile strength and swelling ratio of the SCAI patch that underwent the vitrification process produced in this study are shown. [Figure 14] These are SEM images of various vitrified patches fabricated in this study (scale bars: 1 μm). In Figure 14, "4VOH" indicates a vitrified patch made of VdECM ink (4VOH), "4V0.5H" indicates a vitrified patch made of HAVEM ink (4V0.5H), and "4V1H" indicates a vitrified patch made of HAVEM ink (4V1H). [Figure 15]Schematic diagram of the structure of the multilayered SCAI patch designed in this study for sequential sustained drug release of VEGF and HGF. [Figure 16] The cumulative release profiles of VEGF and HGF were evaluated for one month for each of the two multi-layered SCAI patches designed in this study for sequential sustained drug release of VEGF and HGF. [Figure 17] This shows the results of an in vitro experiment in which a SCAI patch consisting of an outer layer formed using HAVEM Ink (4V0.5H) containing VEGF at a concentration of 0.05 μg / μl as Ink A and an inner core layer formed using HAVEM Ink (4V1H) containing HGF at a concentration of 0.05 μg / μl as Ink B was applied to human brain microvascular endothelial cells (HBMEC) and cultured. [Figure 18] The results show that cell viability was analyzed using a live / dead analysis kit when a SCAI patch consisting of an outer layer formed using HAVEM Ink (4V0.5H) containing VEGF at a concentration of 0.05 μg / μl as Ink A and an inner core layer formed using HAVEM Ink (4V1H) containing HGF at a concentration of 0.05 μg / μl as Ink B was applied to human brain microvascular endothelial cells (HBMEC) and cultured (scale bars: 50 μm). [Figure 19] The results show that angiogenesis-related gene expression levels were analyzed when a SCAI patch consisting of an outer layer formed using HAVEM Ink (4V0.5H) containing VEGF at a concentration of 0.05 μg / μl as Ink A and an inner core layer formed using HAVEM Ink (4V1H) containing HGF at a concentration of 0.05 μg / μl as Ink B was applied to human brain microvascular endothelial cells (HBMEC) and cultured. [Figure 20] This is a schematic diagram of an in vivo experiment in which the SCAI patch in which VEGF and HGF were spatially and temporally compartmentalized, as fabricated in this study, was implanted into the cerebral cortex of SD mice, and the implantation site was monitored using the OR-PAM system. [Figure 21]In this study, in order to track the changes in the SCAI patch over time in an in vivo experiment to evaluate cerebral angiogenesis behavior after SCAI patch implantation, a cross-section of the site where the patch was implanted was photographed in photoacoustic (PA) B-mode (scale bars: 200 μm). [Figure 22] This is an in vivo experiment conducted in this study to evaluate the behavior of cerebral angiogenesis after SCAI patch implantation. The changes in cerebral vascular structure in SD mice treated with or without SCAI patch are shown using photoacoustic (PA) maximum amplitude projection (MAP) images. [Diagram 23] In Fig. 22, the cross-sectional PA B-mode image of the area C1 and C2 indicated by the dotted line in the image of the mouse with the SCAI patch (scale bars: 400 μm) is shown. In the enlarged image in Fig. 23 (scale bars: 1 mm), the large blood vessels are highlighted by an elliptical curve consisting of the following points: [Figure 24] This is the result of a quantitative analysis of blood vessel density in SD mice with and without SCAI patch treatment using optical resolution photoacoustic microscopy (OR-PAM) images in an in vivo experiment to evaluate cerebral angiogenesis behavior after SCAI patch transplantation in this study. [Diagram 25] In this study, an in vivo experiment was conducted to evaluate the behavior of cerebral angiogenesis after SCAI patch implantation. The results of histological analysis of the untreated and SCAI patch implanted groups 14 days after SCAI patch implantation are shown in H&E staining images and immunohistochemistry (IHC) images (CD31) (scale bars: 50 μm). [Figure 26] This study was conducted to evaluate the behavior of cerebral angiogenesis after SCAI patch implantation in an in vivo experiment. The results are the results of a quantitative analysis of the number of blood vessels per unit area in the untreated and SCAI patch-implanted groups using immunohistochemistry (IHC) images 14 days after SCAI patch implantation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be specifically described below.
[0021] The term "bioink" as used herein is defined as a cell compatible material that can be 3-D printed. Bioink can be extruded through a needle at 0-37°C and subsequently gelled or solidified. Bioink can be formulated to be suitable for inkjet, laser-assisted, or microvalve 3-D printing equipment.
[0022] The term "extracellular matrix (ECM)" as used in the present invention refers to the extracellular portion of animal tissues that normally provides structural support to animal cells while also performing a variety of other important functions. The extracellular matrix is composed of various forms of proteins, including collagen, glycosaminoglycan (GAG), etc., as a characteristic that defines connective tissue in animals. Such extracellular matrix may be tissue from animals such as pigs and cows, and can be extracted from a variety of sources.
[0023] The term "biopolymer" used in the present invention is a general term for polymeric compounds synthesized within the bodies of living organisms, representative examples of which include proteins, nucleic acids, and polysaccharides, and specific substances include hyaluronic acid and collagen.
[0024] The term "crosslinking density" used in the present invention is defined as the ratio of the number of structural units (crosslinking points) that are crosslinked in water to the total structural units of a crosslinked polymer. The physical properties of the crosslinked polymer gel, such as swelling degree and elasticity, are significantly affected by the crosslinking density.
[0025] The term "growth factor" as used in the present invention refers to a protein involved in regulating the growth and differentiation of cells or organisms. It acts as a signal transmitter that transmits signals to the inside of the cell by binding to specific receptors present on the cell surface, and regulates various cellular physiological phenomena such as cell differentiation, regeneration, and healing. Specific examples of growth factors include vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), epithermal growth factor (EGF), insulin-like growth factor (IGF), erythropoietin (EPO), fibroblast growth factor (FGF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), keratinocyte growth factor (KGF), interleukin (IL), colony-stimulating factor (CSF), angiopoietin (ANG), platelet-derived growth factor (PDGF), placental growth factor (PGF), transforming growth factor-α (transforming growth factor-α), and the like. These include transforming growth factor-α (TGF-α), transforming growth factor-β (TGF-β), matrix metalloproteinase (MMP), and bone morphogenetic protein (BMP).
[0026] One aspect of the present invention relates to an extracellular matrix-based hybrid ink for 3D printing, which has mechanical properties suitable for 3D printing and can control drug release rate, and a method for producing the same.
[0027] The hybrid ink according to an embodiment of the present invention can be classified as a bioink or biomaterial ink because it is based on a biomaterial that is a cell compatible material. In addition, the hybrid ink according to an embodiment of the present invention is in the form of a composition in which the components are uniformly mixed, and exists in a sol state or an intermediate state between a sol and a hydrogel in order to have the appropriate fluidity required for 3D printing.
[0028] An extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention comprises an extracellular matrix having amine groups and modified hyaluronic acid with introduced ethylenically unsaturated bond functional groups.
[0029] The extracellular matrix may be derived from various organ tissues depending on the purpose of use of the hybrid ink, and is preferably derived from vascular tissue when the purpose of manufacturing an angiogenesis-promoting patch, etc., described later, is taken into consideration. In addition, the extracellular matrix is preferably a decellularized extracellular matrix when the purpose of use is a living body transplantation. The decellularization process has the effect of minimizing immune reactions during allograft or xenograft by removing cells that can act as antigens that induce immune reactions. Since the type and number of cells and the physical properties of the tissue itself differ depending on the tissue, decellularization is performed using various chemicals such as acid, base, hypotonic solution, hypertonic solution, and detergent. In addition, the extracellular matrix may be used while maintaining the structure of the tissue itself after only the decellularization process, or may be dissolved in an acidic solution after freeze-drying and crushing processes, or may be further neutralized to prepare a sol-state solution and used.
[0030] The ethylenically unsaturated bond functional group introduced into the modified hyaluronic acid is not particularly limited as long as it can undergo an aza-Michael addition reaction with an amine group present in the extracellular matrix, and may be selected from, for example, a vinyl group, an allyl group, an acryl group, a methacryl group, etc. In the extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention, the modified hyaluronic acid may be selected from methacrylated hyaluronic acid or acrylated hyaluronic acid, taking into consideration biocompatibility, reactivity with amine groups, etc. The methacrylated hyaluronic acid has a chemical structure represented by the following Chemical Formula 1.
[0031] [Chemical formula 1] TIFF2025500950000002.tif4860
[0032] In the extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention, chemical bonds are formed between at least a portion of the amine groups present in the extracellular matrix and the ethylenically unsaturated functional groups present in the modified hyaluronic acid, so that the components of the hybrid ink, the extracellular matrix and the modified hyaluronic acid, are in a crosslinked state. The chemical bonds between the amine groups present in the extracellular matrix and the ethylenically unsaturated functional groups present in the modified hyaluronic acid are formed by an aza-Michael addition reaction. The aza-Michael addition reaction is a nucleophilic conjugate addition reaction including an N-nucleophile and an electrophile such as an activated alkene, and in the present invention, the amine groups present in the extracellular matrix act as N-nucleophiles, and the ethylenically unsaturated functional groups present in the modified hyaluronic acid act as electrophiles.
[0033] In the extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention, the weight ratio of the extracellular matrix to the modified hyaluronic acid is preferably 1:0.01 to 1:0.8, more preferably 1:0.05 to 1:0.5, in consideration of the chemical crosslinking density, which is a factor related to the mechanical properties, printability, or drug release control of the hybrid ink. In addition, the concentration of the extracellular matrix in the hybrid ink is preferably 1 to 10% (w / v), more preferably 2 to 8% (w / v), in consideration of the mechanical properties, printability, or drug release control of the hybrid ink. In addition, the concentration of the modified hyaluronic acid in the hybrid ink is preferably 0.01 to 8% (w / v), more preferably 0.1 to 4% (w / v), in consideration of the mechanical properties, printability, or drug release control of the hybrid ink.
[0034] In addition, the extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention may further preferably contain a growth factor for the production of a drug delivery patch, an angiogenesis promoting patch, etc., as described below. The growth factor may be selected from various known growth factors depending on a specific application, such as a drug delivery patch manufactured by 3D printing a hybrid ink. For example, the growth factor may be selected from vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), epithermal growth factor (EGF), insulin-like growth factor (IGF), erythropoietin (EPO), fibroblast growth factor (FGF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), keratinocyte growth factor (KGF), interleukin (IL), colony-stimulating factor (CSF), angiopoietin (ANG), platelet-derived growth factor (PGF), and the like. The PDGF, placental growth factor (PGF), transforming growth factor-α (TGF-α), transforming growth factor-β (TGF-β), matrix metalloproteinase (MMP), and bone morphogenetic protein (BMP) may be one or more selected from the group consisting of:The concentration of the growth factor in the hybrid ink may be selected from various ranges depending on the specific application, such as a drug delivery patch manufactured by 3D printing the hybrid ink, and may be, for example, 0.001 to 1 g / L, and is preferably 0.01 to 0.5 g / L in consideration of the drug delivery effect.
[0035] A method for preparing an extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention includes the steps of preparing an extracellular matrix solution having a pH of 6.5 to 7.5, adding modified hyaluronic acid having an ethylenically unsaturated bond functional group to the extracellular matrix solution, mixing the mixture uniformly, and then performing an aza-Michael addition reaction to obtain an ink in which the extracellular matrix and the modified hyaluronic acid are crosslinked. In addition, the method for preparing an extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention may further include the step of adding a growth factor to the ink and mixing the ink so that a patch formed by the ink can be used as a drug delivery system or a disease treatment agent.
[0036] In the method for manufacturing an extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention, the technical features such as the extracellular matrix having an amine group, the modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, the aza-Michael addition reaction, and the growth factor are described above, and detailed description thereof will be omitted.
[0037] In a method for preparing an extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention, the step of preparing an extracellular matrix solution having a pH of 6.5 to 7.5 may be performed by dispersing an extracellular matrix having an amine group in water and then adjusting the pH, or by dissolving an extracellular matrix having an amine group in an acid solution and neutralizing the solution with a base. The type of the acid solution used to dissolve the extracellular matrix is not limited, and is preferably a weak acid solution in consideration of applications such as bioimplantation. The weak acid may be selected from acetic acid, citric acid, butyric acid, palmitic acid, oxalic acid, tartaric acid, malic acid, succinic acid, and the like. In addition, the pH of the extracellular matrix solution is preferably close to neutral in terms of minimizing negative effects on components constituting the ink and smoothly inducing an aza-Michael addition reaction, and may be selected from, for example, 6.8 to 7.4.
[0038] In a method for preparing an extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention, the extracellular matrix and the modified hyaluronic acid are in a crosslinked state after the aza-Michael addition reaction is carried out, because the aza-Michael addition reaction forms chemical bonds between at least a portion of the amine groups present in the extracellular matrix and the ethylenically unsaturated bond functional groups present in the modified hyaluronic acid. The aza-Michael addition reaction is carried out at a temperature of 1 to 10°C, preferably 2 to 8°C, for 2 to 24 hours, preferably 6 to 18 hours, in order to minimize negative effects on the extracellular matrix and the modified hyaluronic acid and smoothly induce the aza-Michael addition reaction.
[0039] In the method for producing an extracellular matrix-based hybrid ink for 3D printing according to one embodiment of the present invention, the amount of modified hyaluronic acid added to the extracellular matrix solution is not significantly limited, but considering the mechanical properties, printability, or drug release control of the hybrid ink, the amount is preferably 1 to 80 parts by weight relative to 100 parts by weight of the extracellular matrix, and more preferably 5 to 50 parts by weight relative to 100 parts by weight of the extracellular matrix. In addition, considering the mechanical properties, printability, or drug release control of the hybrid ink, the concentration of the extracellular matrix in the extracellular matrix solution is preferably 1 to 10% (w / v), and more preferably 2 to 8% (w / v). In addition, the modified hyaluronic acid is preferably added to the extracellular matrix solution to a concentration of 0.01 to 8% (w / v), and more preferably to a concentration of 0.1 to 4% (w / v).
[0040] In a method for preparing an extracellular matrix-based hybrid ink for 3D printing according to an embodiment of the present invention, the amount of growth factor added to the ink may be selected from various ranges depending on the specific application, such as a drug delivery patch prepared by 3D printing the hybrid ink. For example, the growth factor may be added to the ink to a concentration of 0.001 to 1 g / L, and taking into consideration the drug delivery effect, the growth factor may be added to the ink to a concentration of 0.01 to 0.5 g / L.
[0041] One aspect of the present invention relates to a biomaterial-based drug delivery patch having a multi-layer structure in which drugs are spatially and temporally compartmentalized for sequentially releasing different drugs, and a method for manufacturing the same. In another example of the present invention, the technical features of the biomaterial-based drug delivery patch and the method for manufacturing the same, such as the extracellular matrix having an amine group, the modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, the aza-Michael addition reaction, and the growth factor, are described above, and detailed description thereof will be omitted.
[0042] A biomaterial-based drug delivery patch according to one embodiment of the present invention can be fabricated by 3D printing the above-mentioned extracellular matrix-based hybrid ink into a predetermined design structure.
[0043] According to one embodiment of the present invention, a biomaterial-based drug delivery patch is a multi-layered patch including an inner core layer and an outer layer surrounding the inner core layer, the inner core layer and the outer layer being made of an extracellular matrix-based hybrid ink, and the biomaterial-based drug delivery patch exhibits rheological properties corresponding to a hydrogel state or a vitrified gel state.
[0044] In the biomaterial-based drug delivery patch according to an embodiment of the present invention, the hybrid ink includes an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a growth factor. The modified biopolymer may be selected from modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, modified collagen having an ethylenically unsaturated bond functional group introduced therein, and the like. The ethylenically unsaturated bond functional group introduced into the modified biopolymer is not particularly limited in type as long as it can undergo an aza-Michael addition reaction with the amine group present in the extracellular matrix, and may be selected from, for example, a vinyl group, an allyl group, an acrylic group, a methacrylic group, and the like. The modified hyaluronic acid may be selected from methacrylated hyaluronic acid or acrylated hyaluronic acid, taking into consideration biocompatibility, reactivity with amine groups, and the like. In addition, the denatured collagen may be selected from methacrylated collagen or acrylated collagen, taking into consideration biocompatibility, reactivity with amine groups, etc. The methacrylated collagen is a denatured collagen in which a methacryl group is linked to an amine group present in collagen through a peptide bond, and the acrylated collagen is a denatured collagen in which an acrylic group is linked to an amine group present in collagen through a peptide bond. The structure and manufacturing method of the methacrylated collagen or acrylated collagen are disclosed in various publicly known documents (e.g., U.S. Patent Publication No. 8658711; He Liang et al., Journal of Materials Chemistry B, 2018, 6, 3703-3715, etc.).The extracellular matrix and modified biopolymer constituting the hybrid ink are in a chemically crosslinked state. The chemical crosslinking between the extracellular matrix and the modified biopolymer begins with chemical bonds formed between at least a portion of the amine groups present in the extracellular matrix and the ethylenically unsaturated bond functional groups present in the modified hyaluronic acid by an aza-Michael addition reaction.
[0045] In addition, the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer have different chemical crosslinking densities, and in consideration of the sequential sustained release of the drug, it is preferable that the chemical crosslinking density of the extracellular matrix-based hybrid ink constituting the inner core layer is greater than that of the extracellular matrix-based hybrid ink constituting the outer layer. The chemical crosslinking densities of the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer can be adjusted by the weight ratio of the extracellular matrix having an amine group and the modified biopolymer having an ethylenically unsaturated bond functional group, which are components of the extracellular matrix-based hybrid ink. The main component of the extracellular matrix-based hybrid ink is the extracellular matrix, and the greater the amount of the modified biopolymer relative to the extracellular matrix in the hybrid ink, the more chemical bonds are formed by the aza-Michael addition reaction, thereby increasing the chemical bond density. For example, the weight ratio of the extracellular matrix to the modified biopolymer in the extracellular matrix-based hybrid ink constituting the inner core layer is preferably 1:0.2 to 1:0.5. In addition, the weight ratio of the extracellular matrix to the modified biopolymer in the extracellular matrix-based hybrid ink constituting the outer core layer is preferably 1:0.05 to 1:0.15. In addition, the concentration of the extracellular matrix in the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer is preferably 2 to 8% (w / v). In the extracellular matrix-based hybrid ink constituting the inner core layer, the concentration of the modified biopolymer is preferably 0.4 to 4% (w / v). In addition, the concentration of the modified biopolymer in the extracellular matrix-based hybrid ink constituting the outer layer is preferably 0.1 to 1.2% (w / v).
[0046] In addition, the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer contain different growth factors. Thus, in the biomaterial-based drug delivery patch according to one embodiment of the present invention, the inner core layer and the outer layer contain different growth factors. The growth factors may be selected from various known growth factors depending on the specific use of the drug delivery patch. For example, the growth factor may be selected from growth factors that induce angiogenesis, such as vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), epithermal growth factor (EGF), fibroblast growth factor (FGF), angiopoietin (ANG), platelet-derived growth factor (PDGF), placental growth factor (PGF), transforming growth factor-α (TGF-α), transforming growth factor-β (TGF-β), matrix metalloproteinase (MMP), bone morphogenetic protein (BMP), and the like.
[0047] In a biomaterial-based drug delivery patch according to one embodiment of the present invention, when the extracellular matrix-based hybrid ink constituting the inner core layer has a higher chemical cross-linking density than the extracellular matrix-based hybrid ink constituting the outer layer, the growth factors contained in the inner core layer are not only spatially compartmentalized according to the positional relationship with the growth factors contained in the outer layer, but also temporally compartmentalized according to the chemical cross-linking density of the extracellular matrix-based hybrid ink, and the growth factors contained in the inner core layer are gradually released in vivo in a slower order than the growth factors contained in the outer layer. The concentration of the growth factors in the extracellular matrix-based hybrid ink constituting the inner core layer and the extracellular matrix-based hybrid ink constituting the outer layer is preferably 0.01 to 0.5 g / l, taking into account the drug delivery effect of the multi-layered patch.
[0048] A biomaterial-based drug delivery patch according to a preferred embodiment of the present invention is a patch having a multi-layer structure in which a first layer, a second layer, and a third layer are sequentially laminated, and the second layer is composed of a second internal layer located on the inside and two second external layers located on the outside of both sides, and the first layer, the two second external layers, and the third layer are composed of a first hybrid ink, and the second internal layer is composed of a second hybrid ink. The first hybrid ink and the second hybrid ink include an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a growth factor. The extracellular matrix and the modified hyaluronic acid constituting the first hybrid ink and the second hybrid ink are present in a chemically crosslinked state. In addition, the first hybrid ink and the second hybrid ink have different chemical crosslinking densities from each other, and in consideration of the sequential sustained release of the drug, it is preferable that the chemical crosslinking density of the second hybrid ink is greater than the chemical crosslinking density of the first hybrid ink. In addition, the growth factors constituting the first hybrid ink and the second hybrid ink are selected from different growth factors.
[0049] A method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention includes the steps of: preparing a first hybrid ink comprising a mixture of an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state; preparing a second hybrid ink comprising a mixture of an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor different from the first growth factor, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state, the second hybrid ink having a different chemical crosslinking density from the first hybrid ink; 3D printing the second hybrid ink to form an inner core layer; and 3D printing the first hybrid ink to form an outer layer surrounding the inner core layer, thereby obtaining a multi-layer structure. In the method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention, the multilayer structure formed by 3D printing the first hybrid ink and the second hybrid ink and the inner core layer and the outer layer surrounding the inner core layer exists in an intermediate state between sol and hydrogel. The method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention may further include a step of heat treating the multilayer structure at 25 to 45°C, preferably 30 to 40°C, for 0.5 to 3 hours, preferably 0.6 to 1.5 hours, to convert the multilayer structure into a hydrogel state, thereby obtaining a multilayer structure in a hydrogel state. In addition, the method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention may further include a step of drying the multilayer structure in a hydrogel state under a ventilated condition for 6 to 24 hours, preferably 8 to 18 hours, to obtain a vitrified multilayer structure.
[0050] In the method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention, the second hybrid ink preferably has a higher cross-linking density than the first hybrid ink. In the method for manufacturing a biomaterial-based drug delivery patch according to one embodiment of the present invention, the first hybrid ink and the second hybrid ink are extracellular matrix-based hybrid inks that mainly contain an extracellular matrix. The weight ratio of the extracellular matrix to the modified biopolymer in the first hybrid ink is preferably 1:0.05 to 1:0.15. In addition, the concentration of the extracellular matrix in the first hybrid ink is preferably 2 to 8% (w / v), and the concentration of the modified biopolymer is preferably 0.1 to 1.2% (w / v). The weight ratio of the extracellular matrix to the modified biopolymer in the second hybrid ink is preferably 1:0.2 to 1:0.5. In addition, the concentration of the extracellular matrix in the second hybrid ink is preferably 2 to 8% (w / v), and the concentration of the modified biopolymer is preferably 0.4 to 4% (w / v).
[0051] A method for manufacturing a biomaterial-based drug delivery patch according to a preferred embodiment of the present invention includes the steps of: preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor, the extracellular matrix and the modified hyaluronic acid being in a chemically crosslinked state; and preparing a mixture containing an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor different from the first growth factor, the extracellular matrix and the modified hyaluronic acid being in a chemically crosslinked state. The method includes the steps of preparing a second hybrid ink, which is in a chemically crosslinked state and has a different chemical crosslinking density from the first hybrid ink, 3D printing the first hybrid ink to form a first layer, 3D printing the second hybrid ink on the inside of the surface of the first layer, and 3D printing the first hybrid ink on the outside of both sides of the surface of the first layer to form a second layer composed of a second inner layer and two second outer layers, and 3D printing the first hybrid ink on the surface of the second layer to form a third layer, thereby obtaining a multilayer structure. A method for manufacturing a biomaterial-based drug delivery patch according to a preferred embodiment of the present invention may further include a step of heat-treating the multilayer structure including the first layer, the second layer, and the third layer at 25 to 45°C, preferably 30 to 40°C, for 0.5 to 3 hours, preferably 0.6 to 1.5 hours, to obtain a multilayer structure in a hydrogel state. In addition, the method for manufacturing a biomaterial-based drug delivery patch according to a preferred embodiment of the present invention may further include a step of drying the multi-layer structure in a hydrogel state under a ventilated condition for 6 to 24 hours, preferably 8 to 18 hours, to obtain a vitrified multi-layer structure. The first and second hybrid inks have different chemical cross-linking densities, and in consideration of the sequential sustained release of the drug, it is preferable that the chemical cross-linking density of the second hybrid ink is greater than that of the first hybrid ink. In addition, the first and second growth factors constituting the first and second hybrid inks are selected from different growth factors.
[0052] One aspect of the present invention relates to a multi-layered biomaterial-based angiogenesis promoting patch in which drugs are spatially and temporally compartmentalized to sequentially release different angiogenesis promoting factors, and a method for manufacturing the same. Compared with the biomaterial-based drug delivery patch and method for manufacturing the same described above, the biomaterial-based angiogenesis promoting patch and method for manufacturing the same according to the present invention have the same technical features as the above-mentioned biomaterial-based drug delivery patch and method for manufacturing the same, except that the growth factors contained in each layer are embodied as growth factors that promote the early stage of angiogenesis and growth factors that promote the mature stage of angiogenesis.
[0053] A biomaterial-based angiogenesis-promoting patch according to one embodiment of the present invention is a multi-layered patch including an inner core layer and an outer layer surrounding the inner core layer, the outer layer being made of a first hybrid ink based on an extracellular matrix, and the inner core layer being made of a second hybrid ink based on an extracellular matrix. The first hybrid ink includes an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor promoting an early stage of angiogenesis, and the second hybrid ink includes an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor promoting an angiogenesis maturation stage. The extracellular matrix and the modified biopolymer constituting the first hybrid ink and the second hybrid ink are in a chemically cross-linked state, and the second hybrid ink has a higher chemical cross-linking density than the first hybrid ink. In the biomaterial-based angiogenesis-promoting patch according to a preferred embodiment of the present invention, the modified biopolymer having an ethylenically unsaturated bond functional group introduced therein is a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein. In addition, the first growth factor that promotes the initial step of angiogenesis in the biomaterial-based angiogenesis promoting patch according to the present invention may be one or more selected from the group consisting of vascular endothelial growth factor (VEGF), angiopoietin (ANG), platelet-derived growth factor (PDGF), placental growth factor (PGF), epithermal growth factor (EGF), fibroblast growth factor (FGF), transforming growth factor-α (TGF-α), transforming growth factor-β (TGF-β), and matrix metalloproteinase (MMP).In addition, the second growth factor that promotes the maturation stage of angiogenesis may be one or more selected from the group consisting of hepatocyte growth factor (HGF), bone morphogenetic protein (BMP), and transforming growth factor-β (TGF-β).
[0054] A biomaterial-based angiogenesis-promoting patch according to a preferred embodiment of the present invention is a multi-layered patch in which a first layer, a second layer, and a third layer are laminated in order, and the second layer is composed of a second internal layer located on the inside and two second external layers located on the outside on both sides, and the first layer, the two second external layers, and the third layer are composed of a first hybrid ink, and the second internal layer is composed of a second hybrid ink. The first hybrid ink includes an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor that promotes the initial step of angiogenesis. The second hybrid ink includes an extracellular matrix, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor that promotes the maturation stage of angiogenesis. The extracellular matrix and the modified hyaluronic acid that constitute the first hybrid ink and the second hybrid ink are present in a chemically crosslinked state. In addition, the first hybrid ink and the second hybrid ink have different chemical cross-linking densities, and considering the sequential sustained release of the drug, it is preferable that the chemical cross-linking density of the second hybrid ink is greater than the chemical cross-linking density of the first hybrid ink.
[0055] A method for manufacturing a biomaterial-based angiogenesis-promoting patch according to an embodiment of the present invention includes the steps of: preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor that promotes an early stage of angiogenesis, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state; preparing a second hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified biopolymer having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor that promotes a mature stage of angiogenesis, the extracellular matrix and the modified biopolymer being in a chemically crosslinked state, the second hybrid ink having a higher chemical crosslinking density than the first hybrid ink; 3D printing the second hybrid ink to form an inner core layer; and 3D printing the first hybrid ink to form an outer layer surrounding the inner core layer, thereby obtaining a multi-layer structure. In addition, the method for manufacturing a biomaterial-based angiogenesis-promoting patch according to one embodiment of the present invention may further include a step of obtaining a multi-layer structure in a hydrogel state by heat-treating the multi-layer structure including the inner core layer and the outer layer at 25-45° C., preferably 30-40° C. for 0.5-3 hr, preferably 0.6-1.5 hr, in order to convert the multi-layer structure into a hydrogel state. In addition, the method for manufacturing a biomaterial-based angiogenesis-promoting patch according to one embodiment of the present invention may further include a step of drying the multi-layer structure in a hydrogel state under ventilated conditions for 6-24 hr, preferably 8-18 hr, to obtain a vitrified multi-layer structure.
[0056] A method for manufacturing a biomaterial-based angiogenesis-promoting patch according to a preferred embodiment of the present invention includes the steps of: preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a first growth factor promoting an early stage of angiogenesis, the extracellular matrix and the modified hyaluronic acid being in a chemically crosslinked state; and preparing a first hybrid ink comprising a mixture containing an extracellular matrix having an amine group, a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, and a second growth factor promoting a maturation stage of angiogenesis, the extracellular matrix and the modified hyaluronic acid being in a chemically crosslinked state. The method includes the steps of preparing a second hybrid ink, in which the hyaluronic acid is present in a chemically cross-linked state and has a higher chemical cross-linking density than the first hybrid ink; 3D printing the first hybrid ink to form a first layer; 3D printing the second hybrid ink on the inside of a surface of the first layer and 3D printing the first hybrid ink on the outside of both sides of the surface of the first layer to form a second layer composed of a second inner layer and two second outer layers; and 3D printing the first hybrid ink on the surface of the second layer to form a third layer, thereby obtaining a multi-layer structure.
[0057] The biomaterial-based angiogenesis-promoting patch according to the present invention can be used to prevent or treat angiogenesis-dependent diseases. Thus, the present invention provides a biomaterial-based patch for preventing or treating angiogenesis-dependent diseases.
[0058] The "angiogenesis-dependent disease" is a disease accompanied by symptoms of poor blood supply or insufficient angiogenesis. In the present invention, the angiogenesis-dependent disease is not limited to a particular type as long as it is a disease that can be prevented or treated by promoting angiogenesis, and may be, for example, one or more selected from the group consisting of ischemic disease, wound, burn, psoriasis, chronic ulcer, myocardial infarction, angina pectoris, bedsore, alopecia, diabetic retinopathy, retinopathy of prematurity, age-related macular degeneration, glaucoma, diabetic foot ulcer, post-hypertension, and cerebrovascular dementia. In addition, the ischemic disease may be one or more selected from the group consisting of cerebral ischemia, cardiac ischemia, diabetic vascular heart disease, heart failure, myocardial hypertrophy, retinal ischemia, ischemic colitis, ischemic acute renal failure, stroke, brain trauma, and neonatal hypoxia.
[0059] The present invention will be described in more detail with reference to the following examples, which are provided only to clearly illustrate the technical features of the present invention and are not intended to limit the scope of the present invention.
[0060] 1. Experimental Method (1) Production of vascular tissue-derived decellularized extracellular matrix (VdECM) and ink containing the same Fresh porcine aortas purchased from a nearby slaughterhouse were cut into cubes of approximately 2 mm length and washed in deionized water for 6 hours to remove remaining blood. The sliced aortic tissue was then placed in a 0.3% (w / w) sodium dodecyl sulfate solution and stirred for 24 hours, and then placed in a 3% (w / w) Triton X-100 solution and stirred for 24 hours. The aortic tissue was then rinsed in PBS (phosphate buffered saline) solution for 24 hours to wash out the chemical detergent, and then decellularized by treating the aortic tissue with a nuclease solution containing 75 U / ml DNase and 50 mM magnesium chloride (MgCl2) in PBS solution at 37°C for 24 hours. The decellularized tissue was then sterilized by treating it with a 0.1% peracetic acid solution dissolved in 4% ethanol for about 4 hours, and rinsed several times with deionized water and PBS solution to obtain a vascular tissue-derived decellularized extracellular matrix (VdECM).The vascular tissue-derived decellularized extracellular matrix (VdECM) was then rapidly frozen at -80°C and freeze-dried for about 48 hours to obtain a powdered vascular tissue-derived decellularized extracellular matrix (VdECM).
[0061] 100 mg of lyophilized VdECM was dissolved in 7.5 ml of 0.5 M acetic acid solution together with 15 mg of pepsin by stirring at about 120 rpm, and filtered through a mesh filter with a pore size of 40 μm to remove undissolved particles, obtaining a VdECM solution. Then, 10 N sodium hydroxide solution was added to the VdECM solution, and the solution was neutralized to pH 7.4 by stirring to prepare a VdECM ink in a sol state.
[0062] (2) Hybrid ink manufacturing VdECM and methacrylated hyaluronic acid (HAMA) were mixed in a neutral solution (pH 7) and then an aza-Michael addition reaction was carried out at 4°C for about 10 to 12 hours to synthesize a new hybrid bioink in a sol state, which was named "HAVEM ink". The acrylate functional group of the HAMA acts as a Michael acceptor, and the amine functional group present in the VdECM component acts as a Michael donor to carry out an aza-Michael addition reaction. The aza-Michael addition reaction is a nucleophilic conjugate addition reaction that includes N-nucleophiles and electrophiles such as activated alkenes. The aza-Michael addition reaction is known as the simplest and most efficient method of binding amines to α,β-unsaturated carbonyl compounds without the need for a separate catalyst. The HAVEM ink was prepared by adding different amounts of VdECM and methacrylated hyaluronic acid (HAMA) to a neutral solution, and two types of HAVEM inks, HAVEM ink (4V0.5H) and HAVEM ink (4V1H), were prepared. The compositions of the components contained in the two types of HAVEM inks are summarized in Table 1 below. In addition, as a control group, VdECM ink (4VOH) was prepared by adding only VdECM to a neutral solution (pH 7) at a concentration of 4% (w / v).
[0063] [Table 1] TIFF2025500950000003.tif28128
[0064] In addition, to fabricate a spatiotemporal compartmentalized cerebral angiogenesis inducing (SCAI) patch, a total of four types of bioinks were prepared by mixing vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) at concentrations of 0.05 μg / μl each with HAVEM ink (4V0.5H) or HAVEM ink (4V1H).
[0065] (3) Production of SCAI patches To develop a spatiotemporally separated dual growth factor release platform, a three-layered circular patch was fabricated using a 3D printing system. The first layer, the second outer layer, and the third layer were printed using HAVEM ink mixed with VEGF (recombinant human VEGF 165; PeproTech, USA). The second inner layer was printed using HAVEM ink mixed with HGF (recombinant human HGF; PeproTech, USA). The two types of HAVEM ink were loaded into a 3ml syringe equipped with a 24G plastic nozzle (Musashi Engineering Company, Japan), and then loaded into a multi-head 3D printing system (T&R Biofab, Korea). All three layers were printed in a spiral shape by g-code programming at a controlled temperature of 4°C. After printing each layer, a 20-second pause was given to prevent mixing between the stacked layers. For gelation of the printed three-layered circular SCAI patch, it was placed in an incubator at 5% carbon dioxide and 37°C for 1hr. The SCAI hydrogel patch was then dried in a well-ventilated place for about 10 to 12 hours for vitrification, and the vitrified SCAI patch was used for subsequent cell and animal experiments.
[0066] (4) Physicochemical properties of 3D printing ink and SCAI patch Rheological analysis of the 3D printing biomaterial inks prepared above was performed using a Discovery Hybrid Rheometer-2 (TA Instruments, USA) system with a 20 mm cone plate configuration. The 3D printing inks analyzed were three neutralized inks (pH 7): 4% VdECM ink (4V0H); 4% VdECM ink with 0.5% HAMA [HAVEM ink (4V0.5H)], and 4% VdECM ink with 1% HAMA [HAVEM ink (4V1H)]. Shear viscosity values were measured at a temperature of 4 °C and 0.01 s to evaluate the flow behavior of each biomaterial ink. -1 From 1000s -1 The gelation dynamics of each ink was measured under a heating rate of 5°C / min and a shear temperature change mode from 4°C to 37°C. To confirm the storage modulus and loss modulus of the biomaterial ink according to the frequency, a dynamic frequency change test was carried out on the ink gelled at 37°C under a 2% strain condition in the range of 0.1 to 100 rad / s. In addition, to confirm that the ink components VdECM and HAMA were chemically crosslinked through the aza-Michael addition reaction mechanism, the freeze-dried ink was dissolved in D2O and 1 H NMR (400 MHz) spectra were obtained using a Bruker Advance III HD 400 MHz NMR spectrometer. After that, the patch made using the ink was vitrified, and the tensile properties of the vitrified patch were confirmed using an MTS extensometer (AVX54, MTS). In order to prevent the vitrified patch from sliding during the tensile property test, a rectangular vitrified patch sample (25 mm x 8 mm x 400 μm) was prepared and fixed using a screw grip attached to the MTS extensometer.
[0067] (5) Growth factor release test Recombinant human VEGF 165 (100-20; PeproTech, USA) and recombinant human HGF (100-39H; PeproTech, USA) were mixed into each ink to a final concentration of 0.05 μg / μl, and then multi-layered patches were laminated by 3D printing, followed by heat treatment and drying to produce vitrified SCAI patches. The vitrified SCAI patches underwent double crosslinking, i.e., chemical crosslinking and thermal crosslinking. The vitrified circular disk-shaped (8 mm diameter, 150 μm height) SCAI patches were placed in 1.1 ml of PBS solution at 37°C. After that, 1 ml of the solution was taken at each desired time point and stored at -80°C, and the PBS solution was added in the same amount as that taken. Then, the amount of growth factors VEGF (DY293B; R&D Systems, USA) and HGF (DY294; R&D Systems, USA) released from each patch was quantified using an ELISA kit.
[0068] (6)Cell culture Human brain microvascular endothelial cells (HBMECs; Innoprot, Korea) were seeded in endothelial cell medium (ECM; Innoprot, Korea) supplemented with 5% (v / v) fetal bovine serum, 1% (v / v) endothelial cell growth supplement, and 1% (v / v) penicillin / streptomycin, and cultured at 5% carbon dioxide and 37°C with medium replacement every 2-3 days. When the confluence reached 90%, the cells were washed with DPBS (Dulbecco's phosphate-buffered saline) and treated with 0.25% Trypsin-EDTA (Gibco, USA) solution at 5% carbon dioxide and 37°C for 4 minutes, and then the cells were isolated and used.
[0069] (7) RT-PCR Using 12-well plates, place HBMEC cells at 1.5 x 10 cells per well in 1.5 ml of medium. 4The cells were cultured at a density of 1000 x 1000 mm. In the experimental group, a SCAI patch was placed on a transwell inserted into the well to confirm the effect of growth factors released by the patch on the growth of HBMECs. On days 3, 7, and 14 of culture, mRNA from the cells in the well was extracted using RNAiso plus (Takara Bio, Japan). The extracted RNA concentration and purity were measured using a Nanodrop Lite spectrometer (Thermo Fisher Scientific, USA). Then, the extracted mRNA was reverse transcribed using the SuperScript IV First-Strand Synthesis System (Invitrogen Life Technologies, USA). Real-time PCR was performed using a StepOne Plus Real-Time Cycler (Applied Biosystems, USA) with SYBR-green I reagent (Takara, Japan). Data were analyzed using StepOne software.v2.3, and the expression level of each gene normalized to GAPDH expression was 2 -ΔΔCT The primer sequences used in the real-time PCR were designed based on gene sequences published in NCBI and PubMed, and the primer sequences used in the real-time PCR are summarized in Table 2 below.
[0070] [Table 2] TIFF2025500950000004.tif114157
[0071] (8) Evaluation of the effect of SCAI patches on cell experiments To evaluate in vitro cytotoxicity, a released SCAI patch was placed on a transwell inserted into each well, and 2 × 10 HBMECs were placed on the bottom of each well. 4The cells were then cultured for 7 days at 5% carbon dioxide and 37°C, and stained using a live / dead assay kit (LIVE / DEAD Cell Viability Assay, Thermo Fisher Scientific, USA). Live and dead cells were labeled with green and red fluorescent substances, respectively, and observed under a fluorescent microscope (Nikon Instruments, Japan). Cell proliferation was quantified using a Cell Counting Kit-8 Assay Kit (Dojindo Molecular Technologies, Japan). After culturing the cells for a specific time for each of the experimental group with the patch and the control group without the patch, they were incubated with a CCK-8 solution diluted 1:10 in fresh medium at 37°C for 3 hr. The treated solution was then transferred to a clear 96-well plate, and the absorbance at 450 nm was measured using a Multiskan™ GO Microplate Spectrophotometer (Thermo Fisher Scientific, USA).
[0072] (9) Evaluation of the effect of SCAI patches on animal testing All animal studies were performed in accordance with nationally prescribed guidelines after approval by the local Institutional Animal Care and Use Committee (POSTECH-2021-0022). Eight-week-old male Sprague-Dawley (SD) mice weighing 200–300 g were used for in vivo experiments. Mice were anesthetized using an anesthesia induction chamber containing 4.0% isoflurane initially and then maintained at 1.5% isoflurane concentration during surgery. The head was fixed with ear bars on a stereotaxic frame, and body temperature was maintained with a heating pad. After shaving the head, the skin of the hemisphere was incised. The remaining epidermis and remnants were removed with saline solution. Then, a craniotomy was carefully performed using a dental drill. The exposed brain tissue was completely covered with a PDMS (Polydimethylsiloxane) membrane with a size of 6 mm × 11 mm and a thickness of 150–180 μm, sterilized, and then immersed in saline solution. The border of the PDMS membrane was attached to the skull using a cyanoacrylate adhesive (Loctite, USA). Then, dental resin (OA2; Denkist Inc., Korea) was applied along the edge of the PDMS membrane and exposed to UV light for 15 seconds to semi-permanently attach it to the skull. Finally, the mice were given Baytril (5 mg / kg; Bayer, Germany) via subcutaneous injection and returned to their cages. Then, Tylenol (0.5 mg / ml; Janssen, Korea) and Marboxyl (0.06 mg / ml; Vetoquinol, Korea) were continuously provided through drinking water to alleviate inflammation. Two weeks after surgery, brain tissue was collected and analyzed using hematoxylin / eosin (H&E) staining and immunohistochemistry (IHC), and the functional angiogenesis efficacy of the SCAI patch was evaluated based on the results.
[0073] (10) Photoacoustic monitoring of cerebral angiogenesis induced by SCAI patch To monitor cerebral angiogenesis, an optical resolution photoacoustic microscope (OR-PAM) system (OptchoM, Optcho, Korea) was used. OR-PAM is a bioimaging tool for non-invasive exploration of volumetric microvessels, which generates ultrasound waves in blood vessels using a 532 nm wavelength nano-pulse laser system (VPFL-G-10, Spectra-Physics, USA). The ultrasound waves generated by the system are measured by a customized ultrasound transducer with a central frequency of 20 MHz and a bandwidth of 60%. A wide field of view (FOV) image can be reconstructed by combining the segmented images. The segmented images were acquired using a galvanometer scanner (GVS001; Thorlabs, USA) and two linear motorized stages (L-509.10SD00; Physik Instrumente, Germany). The galvanometer scanner adjusts the laser pulse with a scanning range length of 1.6 mm (400 pixels) and a scanning speed of 50 Hz. A linear motorized stage (step size 5μm) with a maximum scanning range of 26mm moves the scanning part of the OR-PAM system in a direction perpendicular to the scanning direction of the galvanometer scanner. The scanning range of the stage is adjusted according to the size of the ROI. Another linear stage moves the scanning part in the same scanning direction as the galvanometer scanner to provide a segmented image in another region. The acquired segmented image was reconstructed with a wide-angle FOV image by a structural similarity (SSIM)-based volumetric image registration algorithm using pyramid blending. To calculate the density of newly generated blood vessels with a diameter of less than 50μm, a mask was first created to remove the area outside the ROI, and then blood vessels with a diameter of more than about 150μm were removed from the PA maximum amplitude projection (MAP) image of the mouse brain. The area of the ROI was calculated as the area of the mask. Then, a Hessian-based vascular filter was applied to extract blood vessels with a diameter of more than 50μm in the filtered image, and a large vascular map was generated based on the extracted blood vessels. Finally, the large vessel map was removed from the vascular filtering image, and a small vessel map was reconstructed from small vessels with a diameter of less than 50 μm, and the area of the small vessels was calculated based on the small vessel map.
[0074] (11)Histological analysis The brains were removed, the tissue samples were fixed in 4% paraformaldehyde solution, and the surgical site where the patch was attached was dissected. After that, the tissue samples were set in paraffin, and the paraffin-containing tissue samples were cut transversely at a thickness of less than 5 μm for H&E staining experiments. The stained images were imaged using a microscope system (Leica DM750; Leica).
[0075] (12) Immunohistochemistry Tissue samples fixed in 4% paraformaldehyde solution were hardened in paraffin and sectioned at 4 μm thickness for immunofluorescence staining. Then, deparaffinization and rehydration steps were performed using a buffer solution. The sections were then incubated in 10% hydrogen peroxide solution at room temperature for 10 min and stained with a primary antibody against CD31 (1:1000; Abcam, UK). The stained areas were further incubated with a peroxidase-conjugated secondary antibody (Envision+Rabbit; DAKO, USA) for 30 min, and Mayer's Hematoxylin was applied for contrast staining. The resulting slides were imaged using a microscope system (Leica DM750; Leica).
[0076] (13) Statistical analysis All statistical analyses were performed using the GraphPad Prism 8.2.1 program (GraphPad Software, USA). The significance of differences between data was evaluated through two-way ANOVA or t-test. The expressions of statistical significance are as follows: *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001.
[0077] 2. Experimental Results Figure 1 shows the schematic process of fabricating hybrid ink (HAVEM ink) from vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) using a dual crosslinking mechanism, i.e., chemical crosslinking and thermal crosslinking, in this study. Figure 2 shows the schematic process of fabricating a spatiotemporal compartmentalized cerebral angiogenesis inducing (SCAI) patch using a 3D printing process after adding cerebrovascular growth factors VEGF and HGF to hybrid inks with different crosslinking densities in this study, and the schematic process of sequentially releasing VEGF and HGF in the SCAI patch.
[0078] As can be seen from Figures 1 and 2, the inventors of the present invention have fabricated an elaborate SCAI hydrogel patch that allows two angiogenic growth factors to be compartmentalized and released sequentially in a delayed manner by utilizing an extracellular matrix (ECM)-based hybrid ink and 3D printing technology. A hybrid ink was formed by bonding vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) using a chemical crosslinking method called aza-Michael addition reaction. The aza-Michael addition reaction is an ideal mechanism for fabricating SCAI patches because it does not require an exogenous catalyst and can easily adjust the release pattern and printability of angiogenic factors by simply changing the chemical bond density. The inventors of the present invention arranged different growth factors inside and outside the SCAI arrangement, respectively, to sequentially release growth factors after implantation, and used two types of hybrid inks (HAVEM inks) with different chemical crosslinking densities to load the different growth factors. The two types of hybrid inks (HAVEM inks) loaded with different growth factors were 3D printed to manufacture an SCAI patch, and then a vitrification process was applied to the SCAI patch to create a soft, flexible, and easy-to-handle patch for brain implantation. It was demonstrated in vitro and in vivo that the patch thus fabricated has a therapeutic effect of promoting angiogenesis. In particular, the inventors of the present invention used a photoacoustic microscope with a non-labeling method to observe the angiogenesis pattern of cerebral microvessels over time for 14 days after patch implantation. Quantitative results showed that the SCAI patch showed considerable angiogenesis performance in the brain region.
[0079] (1) Physicochemical properties of hybrid ink (HAVEM ink) To load and release angiogenic factors in the patch at the desired amount and speed, a new biomaterial-based dual crosslinked hybrid ink was prepared from HAMA and VdECM, which we named "HAVEM ink." Figure 3 shows a schematic diagram of the process of preparing HAVEM ink from vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) through an aza-Michael addition reaction. First, in the chemical crosslinking process of HAVEM ink, the methacrylate group of HAMA and the amine group of VdECM are bonded through the aza-Michael addition reaction. The chemical crosslinking density could be adjusted by adjusting the ratio of each VdECM and HAMA.
[0080] The chemical bonds formed through the aza-Michael addition reaction were confirmed by NMR spectroscopy. Figure 4 shows the spectra of VdECM ink (4V0H), HAMA and HAVEM ink (4V0.5H) measured by nuclear magnetic resonance (NMR) to prove the occurrence of crosslinking between VdECM and methacrylated hyaluronic acid (HAMA). The NMR characteristic peaks associated with the methacrylate functional groups are highlighted at 1.9, 5.7 and 6.1 ppm.
[0081] In the NMR spectrum of HAMA, peaks at 1.9, 5.7, and 6.1 ppm were observed, which are the NMR characteristic peaks of the methacrylate groups contained in HAMA, but in the spectrum of the ink containing only VdECM (4V0H), these peaks were not observed at the same positions, indicating the absence of methacrylate groups. Additionally, in the HAVEM ink groups (4V0.5H and 4V1H), no NMR characteristic peaks corresponding to methacrylate groups could be observed. This means that all of the methacrylate groups in HAMA successfully reacted with the amine groups of VdECM to form chemical crosslinks.
[0082] We then confirmed the change in printability depending on the proportion of HAMA in HAVEM ink. The photographs above in Figure 5 are images of the sol state of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) with different chemical cross-linking densities, and the graph below Figure 5 shows the results of measuring the viscosity of VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) at various shear rates and printing conditions of 4°C. As can be seen from Figure 5, the HAVEM inks (4V0.5H and 4V1H) with different chemical cross-linking densities all had slightly higher viscosities than the ink containing only VdECM (4V0H), and showed shear thinning characteristics in rheology. More specifically, as the chemical cross-linking density increased, the ink fluidity decreased and the viscosity increased. Meanwhile, the viscosity of each HAVEM ink was hardly affected by changes in time.
[0083] To confirm the effect of controlled crosslink density on the mechanical properties of HAVEM ink, the change in the complex modulus of the ink was monitored by increasing the temperature of the HAVEM ink from 4°C to 37°C. Figure 6 shows the change in the elastic modulus of the VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) as the temperature changed from 4°C to 37°C. The change in the elastic modulus in Figure 6 allows the gelation kinetics of the ink to be understood. As can be seen from Figure 6, the complex modulus of the HAVEM ink (4V1H) containing a higher HAMA concentration showed a tendency to increase more significantly as thermal crosslinking progressed compared to the HAVEM ink (4V0.5H) containing a lower HAMA concentration and the VdECM ink (4VOH) containing VdECM alone. The time required to reach equilibrium was observed to be relatively longer for the HAVEM ink (4V1H), which has a higher chemical crosslink density than the other inks (4V0.5H, 4V0H), which is presumed to be because the increased proportion of HAMA in the ink leads to more chemical crosslinks, resulting in a larger complex modulus. At equilibrium, the complex modulus of the HAVEM ink (4V1H) was observed to be 1.91 and 3,045 times larger than the HAVEM ink (4V0.5H) and VdECM ink (4VOH).
[0084] Next, when the complex modulus of the ink in the gel state after chemical and thermal crosslinking was confirmed, the HAVEM (4V1H) ink showed a complex modulus value greater than that of the VdECM (4V0H) and HAVEM (4V0.5H) inks. Figure 7 shows the storage and loss moduli of the VdECM ink (4V0H), HAVEM ink (4V0.5H), and HAVEM ink (4V1H) at a temperature of 37 °C according to the change in vibration frequency. As can be seen from Figure 7, it was confirmed that the hybrid ink has higher structural fidelity as the crosslinking rate is higher during the printing process. The chemical crosslinking density of the HAVEM ink can be changed to induce it to have appropriate mechanical properties, which has a direct effect on regulating the release profile of the angiogenic factor. Figure 8 shows the release profile of HGF encapsulated in HAVEM ink (4V0.5H) and HAVEM ink (4V1H) measured for 7 days. As can be seen from FIG. 8, it was confirmed that the HGF release from HAVEM ink containing HGF (4V1H) was much slower than the HGF release from HAVEM ink containing HGF (4V0.5H).
[0085] (2) Design and fabrication of a SCAI patch using 3D printing technology To make the SCAI patch, two types of HAVEM ink, HAVEM ink (4V0.5H) and HAVEM ink (4V1H), were used. Figure 9 shows the schematic diagram of the process of making the SCAI patch using 3D printing technology in this study. As can be seen from Figure 9, the patch structure was designed to have a circular shape with a total of three layers, which are divided into an outer layer and an inner layer, and 3D printed. The outer layer was loaded with VEGF (an angiogenesis factor involved in the early step of angiogenesis) so that it could be released early, and the inner layer was designed to apply HGF (an angiogenesis factor involved in the late angiogenesis process) so that it could be released delayed. Figure 10 shows the results of measuring the angiogenic effect of various angiogenesis factors by tube formation assay. Figure 10 A shows a schematic diagram of the tube formation assay, and Figure 10 B shows the total tube length measured after 48 hours for the untreated group (control), VEGF, HGF, and VEGF and HGF combination treated samples. As can be seen from FIG. 10, the combination of growth factors effectively induced rapid and extended tube formation in human brain microvascular endothelial cells (HBMECs), forming the highest total tube length after 48 hours compared to the group treated with only one type of growth factor. Based on these results, a circular SCAI patch with a diameter of 8 mm was fabricated using HAVEM ink containing VEGF (4V0.5H; ink A) and HAVEM ink containing HGF (4V1H; ink B). First, ink A was printed along a spiral track with a diameter of 8 mm to form the first layer. In order to physically block HGF from the outside, ink B was printed along a spiral track with a diameter of 6 mm at the inner position of the first layer to form the second inner layer, and then the second outer layer and the third layer were printed using ink A under the same printing conditions. After printing each layer, the printing was paused for 20 seconds, the Z axis was raised by 200 μm, and the next layer was printed.As a result, HGF was not only spatially compartmentalized during the printing process, but also temporally compartmentalized using HGF-containing ink, HAVEM ink (4V1H), thereby preventing HGF from being released from the patch during the early steps of angiogenesis. In this study, the inner core layer was printed with HAVEM ink (4V1H; ink B) containing HGF and the outer layer completely surrounding the core layer was printed with HAVEM ink (4V0.5H; ink A) containing VEGF and low cross-linking density. Meanwhile, since the first layer, second outer layer, and third layer of the patch were all made of HAVEM ink (4V0.5H; ink A) containing VEGF, VEGF was released immediately after the patch was implanted, amplifying its effect on the early angiogenesis process.
[0086] Figure 11 shows the cross-sectional structure of the SCAI patch produced in this study and images of each cross-section taken with a confocal microscope (scale bars: 200 μm). Figure 12 shows the design structures of SCAI patches produced with various combinations of HAVEM inks and images of each patch during the printing, gelation, and vitrification steps. In Figure 12, the patch of design structure 1 (leftmost column) was produced by printing in a circular shape using VdECM ink (4VOH), the patch of design structure 2 (middle column) was produced by printing the inner core layer with HAVEM ink (4V1H) and the outer layer surrounding the inner core layer with HAVEM ink (4V0.5H), and the patch of design structure 3 (rightmost column) was produced by printing in a lattice shape using HAVEM ink (4V0.5H) (scale bars: 10 mm). As can be seen from Figures 11 and 12, the compartmentalized structure of the patch was well maintained even after the patch was printed and then subjected to a thermal crosslinking process. This proves that HAVEM ink has excellent printability and can easily print desired structures even using a multi-material-based printing process. In fact, it was relatively difficult to achieve an accurate shape when printing with VdECM ink (4V0H) compared to HAVEM ink (4V0.5H), so it was not easy to print the desired SCAI patch shape. In contrast, it was confirmed that HAVEM ink (4V0.5H) can print not only a compartmentalized SCAI patch structure, but also a lattice-type hydrogel structure with a double-layer micropore structure. Therefore, when using the HAVEM ink prepared in this study, patches with various structures can be manufactured.
[0087] The inner core layer was printed with HAVEM ink (4V1H), and the outer layer surrounding the inner core layer was printed with HAVEM ink (4V0.5H) to form a SCAI patch, which was then thermally crosslinked through a prescribed heat treatment and then vitrified to facilitate implantation during surgery, handling, and storage. The tensile stress-strain properties were investigated to evaluate the mechanical properties of the SCAI patch that underwent the vitrification process. Figure 13 shows the tensile strength measurement results and swelling ratio of the SCAI patch that underwent the vitrification process fabricated in this study. In Figure 13, "Control" shows the SCAI patch that did not undergo the vitrification process, and "SCAI patch" shows the SCAI patch that underwent the vitrification process. As can be seen from Figure 13, the vitrified SCAI patch exhibited a tensile strength of 18.62 MPa, which is 12.46 times higher than the control sample that did not undergo the vitrification process. In addition, when immersed in saline, the vitrified patch quickly reabsorbed water and expanded up to 151%. The microstructure of the vitrified SCAI patch was imaged using a scanning electron microscope (SEM), and it was possible to confirm the interconnected structure and porous structure that changed depending on the crosslinking density. Figure 14 shows SEM images of various vitrified patches fabricated in this study (scale bars: 1 μm). In Figure 14, "4VOH" indicates a vitrified patch made of VdECM ink (4VOH), "4V0.5H" indicates a vitrified patch made of HAVEM ink (4V0.5H), and "4V1H" indicates a vitrified patch made of HAVEM ink (4V1H). As can be seen from Figure 14, the density of the fiber morphology increases as the crosslinking density increases, and it was confirmed that the density of the fiber morphology on the SEM image also increases as the crosslinking density increases in each structure in the order of 4V0H, 4V0.5H, and 4V1H.
[0088] (3) In vitro experiments to evaluate the sustained and sequential release profile and cellular behavior of SCAI patches After establishing the characteristics of the SCAI patch, the inventors of the present invention confirmed the release profile of growth factors from the fabricated patch. In order to ensure the sequential release of VEGF and HGF, two strategies were used. The chemical crosslinking density of the HAVEM ink containing each growth factor was adjusted, and a hydrogel patch was fabricated using 3D printing technology that allows the two angiogenic factors to be compartmentalized in time and space.
[0089] A hydrogel with a low chemical crosslinking density contains more water and therefore degrades faster than a hydrogel with a high chemical crosslinking density. Based on this principle, the higher the density of chemical crosslinking of the hydrogel, the slower the release rate of the growth factors encapsulated in the hydrogel. Since the SCAI patch of the present invention is a chemically crosslinked hydrophilic matrix, the decomposition rate can be controlled by adjusting the density of chemical bonds, which in turn allows the release pattern of the growth factors loaded in the hydrogel to be controlled.
[0090] To verify the above-mentioned strategy designed for the sequential drug release of VEGF and HGF, two types of multi-layered SCAI patches were fabricated and the release patterns of growth factors were confirmed for two experimental groups. Figure 15 shows a schematic structure of the multi-layered SCAI patch designed in this study for the sequential drug release of VEGF and HGF. As can be seen from Figure 15, the multi-layered SCAI patch designed in this study is composed of an inner core layer made of hybrid ink containing HGF (ink B) and an outer layer made of hybrid ink containing VEGF (ink A) surrounding the inner core layer. Figure 16 shows the cumulative release profiles of VEGF and HGF for each of the two types of multi-layered SCAI patches designed in this study for the sequential drug release of VEGF and HGF, evaluated for one month. The left experimental group in FIG. 16 is composed of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a concentration of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V0.5H) containing HGF at a concentration of 0.05 μg / μl as ink B, and is the result of observing the drug sustained release and sequential release patterns for a multi-layer SCAI patch in which the drug is only spatially compartmentalized under the same ink conditions. The right experimental group in FIG. 16 is composed of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a concentration of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V1H) containing HGF at a concentration of 0.05 μg / μl as ink B, and is the result of observing the drug sustained release and sequential release patterns for a multi-layer SCAI patch in which the drug is spatially and temporally compartmentalized. As can be seen from Figure 16, VEGF loaded in the outer layer of the SCAI patch was released within one day (24 hours) at 50.07% ± 10.63% in both groups, with no significant difference between the two groups. Meanwhile, HGF loaded in the inner core layer of the SCAI patch was located in the inner layer, which was relatively protected from erosion by water, in both groups, and therefore showed a slower release than VEGF.Furthermore, as can be seen from the experimental group on the right, when the chemical crosslink density of the HAVEM ink was adjusted to create a difference between the external and internal conditions in terms of materials as well, it was confirmed that sustained and sequential release patterns were more evident than when only spatial division was achieved.In the experimental group on the right, where the chemical crosslink density of the external and internal layers was adjusted and HGF was loaded into a different HAVEM ink (4V1H) from the external layer, it took 30 days to release approximately 50% of the initial HGF loading, whereas in the experimental group on the left, where the chemical crosslink density of the external and internal layers was not adjusted and HGF was loaded into the same HAVEM ink (4V0.5H) as the external layer, it took about 4 days for HGF to release an amount similar to that of the experimental group on the right.
[0091] To evaluate the therapeutic potential of the SCAI patch by promoting angiogenesis, biocompatibility and in vivo function were verified through in vitro experiments. FIG. 17 shows the results of an in vitro experiment in which a SCAI patch consisting of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a content of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V1H) containing HGF at a content of 0.05 μg / μl as ink B was applied to human brain microvascular endothelial cells (HBMEC) and cultured. In the in vitro experiment of FIG. 17, HBMEC cells were cultured with the SCAI patch placed on a transwell. As can be seen from FIG. 17, when the SCAI patch was applied to human brain microvascular endothelial cells (HBMEC) and cultured for 7 days, it was confirmed that there was no adverse effect on cell viability and that the proliferation rate of human brain microvascular endothelial cells (HBMEC) was promoted compared to the untreated group. Figure 18 shows the results of analyzing cell viability using a live / dead analysis kit when a SCAI patch consisting of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a content of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V1H) containing HGF at a content of 0.05 μg / μl as ink B was applied to human brain microvascular endothelial cells (HBMEC) and cultured (scale bars: 50 μm). The cell proliferation results in Figure 17 were cross-validated through the live / dead staining analysis results in Figure 18. Figure 19 shows the results of analyzing the expression levels of angiogenesis-related genes when SCAI patches consisting of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a content of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V1H) containing HGF at a content of 0.05 μg / μl as ink B were applied to human brain microvascular endothelial cells (HBMECs) and cultured. As can be seen from Figure 19, in the early stage of angiogenesis, the group to which the SCAI patch was applied showed higher expression of angiogenesis-related genes compared to the untreated group, but the difference was not significant.Meanwhile, the expression of all angiogenesis-related gene markers, including FLT1, FLK1, ANGPT1, and PECAM, increased rapidly 14 days after application of the SCAI patch. These results indicate that the SCAI patch has a strong effect on promoting angiogenesis. VEGF and HGF released by the SCAI patch affect HBMEC cells, and the delayed release of HGF works in synergy with VEGF to effectively generate blood vessels.
[0092] (4) In vivo experiments to evaluate cerebrovascularization behavior after SCAI patch implantation In order to evaluate the in vivo therapeutic potential of the SCAI patch, which is composed of an outer layer formed using HAVEM ink (4V0.5H) containing VEGF at a content of 0.05 μg / μl as ink A and an inner core layer formed using HAVEM ink (4V1H) containing HGF at a content of 0.05 μg / μl as ink B, the angiogenesis behavior of the cerebral blood vessels induced by the SCAI patch was visualized over time using the OR-PAM system. Figure 20 shows a schematic diagram of an in vivo experiment consisting of a process in which the SCAI patch in which VEGF and HGF were spatiotemporally compartmentalized as prepared in this study was implanted into the cerebral cortex of an SD mouse and the implanted site was monitored using the OR-PAM system. The inventors of the present invention anesthetized the mouse, performed a craniotomy, removed the skull, and implanted the SCAI patch into the cerebral part. Thereafter, a thin PDMS membrane was covered at the implanted site to allow the penetration of laser and photoacoustic (PA) ultrasound for monitoring. Thereafter, photoacoustic imaging was performed on the areas of interest of the mice for 14 days to monitor changes in blood circulation and cortical microvascular structure in the mouse brain.
[0093] Figure 21 shows a photoacoustic (PA) B-mode image (scale bars: 200 μm) of a cross section of the site where the patch was implanted to track changes in the SCAI patch over time in an in vivo experiment to evaluate cerebrovascularization behavior after SCAI patch implantation in this study. In Figure 21, the PA signal is weak inside the translucent SCAI patch due to low absorption of the laser beam, so the boundary of the patch was determined based on this and highlighted with a yellow dotted line. As can be seen from Figure 21, the patch thickness on day 0 of implantation was displayed as 140 μm, similar to the thickness of the vitrified SCAI patch. One day after implantation, the patch expanded with cerebrospinal fluid and the patch thickness increased to 240 μm. Thereafter, the patch degraded, decreasing to about 70 μm on day 7 of implantation, making it almost indistinguishable in the PA B-mode image. In addition, 14 days after implantation, the patch was completely degraded and the patch was no longer observed in the PA B-mode image (result images not shown).
[0094] Figure 22 shows the photoacoustic (PA) maximum amplitude projection (MAP) images of the cerebral vascular structure changes in SD mice with and without SCAI patch treatment in an in vivo experiment to evaluate cerebral angiogenesis behavior after SCAI patch implantation in this study, and Figure 23 shows cross-sectional PA B-mode images of areas C1 and C2 indicated by dotted lines in the image of a mouse with a SCAI patch applied in Figure 22 (scale bars: 400 μm). In the enlarged image (scale bars: 1 mm) of Figure 23, large blood vessels are highlighted by elliptical curves consisting of the following points. As can be seen from Figures 22 and 23, the implanted SCAI patch induced angiogenesis, and it was possible to observe that the cerebral microvascular structure changed over time. 14 days after implantation, it was possible to confirm that many microvascular structures were newly growing at the SCAI patch implantation site, and many newly formed blood vessels with a diameter of 50 μm or less were observed due to the synergistic effect of the released VEGF and HGF. On the other hand, no significant changes in the microvascular structure could be observed in the SCAI patch untreated group. The original blood vessels partially covered by the newly generated blood vessels can be confirmed through the magnified image in Fig. 22. The hidden original blood vessels are highlighted by dotted lines in the C1 and C2 regions in the MAP image in Fig. 22, and can be clearly seen in Fig. 23, which is a PA B-mode image of the C1 and C2 regions shown in Fig. 22. In Fig. 23, the contours of the original blood vessels and the newly generated blood vessels are displayed as an elliptical curve consisting of the points below and a curve consisting of the points above, respectively.
[0095] Quantitative analysis of the density of newly formed blood vessels was also carried out. Figure 24 shows the results of a quantitative analysis of blood vessel density in SD mice treated with or without SCAI patch treatment using optical resolution photoacoustic microscopy (OR-PAM) images in an in vivo experiment to evaluate the behavior of cerebral angiogenesis after SCAI patch implantation, performed in this study. Blood vessel density was determined as the ratio of the area of blood vessels with a diameter of less than 50 μm to the grafted surface area. As can be seen from Figure 24, when comparing the density obtained before and 14 days after SCAI patch implantation, the blood vessel density after patch implantation was 0.0609 ± 0.0052 mm on the 14th day after implantation. 2 / mm 2to 0.1999±0.0239mm 2 / mm 2 These results suggest that the SCAI patch prepared in this study has therapeutic efficacy in promoting cerebral angiogenesis.
[0096] The inventors of the present invention also performed histological evaluation to verify the angiogenesis efficacy of the SCAI patch, which showed similar results to those observed in the PAM images. Figure 25 shows the histological analysis results of the untreated and SCAI patch groups 14 days after SCAI patch implantation in an in vivo experiment to evaluate the cerebral angiogenesis behavior after SCAI patch implantation, using H&E staining images and immunohistochemistry (IHC) images (CD 31) (scale bars: 50 μm). The scale bars of the enlarged images in Figure 25 are 20 μm. As can be seen from Figure 25, in the SCAI patch implanted group, large blood vessels that could supply blood to the surrounding tissues at the patch implantation site remained 14 days after patch implantation, and numerous capillaries of various diameters and lengths were also observed (shown by black arrows). Some of the blood vessels showed signs of extending from the original large vessels, which is clear evidence of angiogenesis (shown by gray arrows). On the other hand, in the SCAI patch untreated group, no vascular features extending from the large blood vessels could be observed. The inventors of the present invention also cross-validated the angiogenic effect of the implanted patch using immunohistochemistry (IHC) against mouse-specific vascular antibodies, and observed a similar tendency to the H&E staining results (indicated by black arrows). The inventors of the present invention also cross-validated the angiogenic effect of the implanted patch using immunohistochemistry (IHC) against mouse-specific vascular antibodies, and observed a similar tendency to the H&E staining results (indicated by black arrows) in the unit area (1 mm 2 ) to quantify the degree of angiogenesis. Figure 26 shows the results of a quantitative analysis of the number of blood vessels per unit area in the untreated group and the SCAI patch grafted group using immunohistochemistry (IHC) images 14 days after SCAI patch grafting in an in vivo experiment conducted in this study to evaluate the behavior of cerebral angiogenesis after SCAI patch grafting. As can be seen from Figure 26, the number of blood vessels per unit area in the SCAI patch grafted group was 167 ± 13, while the number of blood vessels in the untreated group was 29 ± 5, resulting in a blood vessel count of 1 mm2 or less in the SCAI patch grafted group.2 Approximately 5.76-fold more blood vessels were generated per unit time. Taken together, it can be concluded that the SCAI patch promotes angiogenesis and neovascularization and maintains therapeutic efficacy for at least 14 days in vivo.
[0097] 3. Discussion and Conclusion The inventors of the present invention have fabricated a flexible patch-type drug delivery system that can release two angiogenic factors through the angiogenesis step to promote cerebral angiogenesis in the brain region. The main features of the fabricated SCAI patch are as follows:
[0098] (1) The HAVEM ink used to fabricate the patches can variably tune the release profile by varying the bond density between the methacrylate and amine functional groups.
[0099] (2) 3D printing technology can be used to spatially and temporally compartmentalize and sequentially release angiogenic growth factors.
[0100] Existing biofabrication strategies (e.g., mold casting, gas foaming, and freeze-drying) have been widely applied to produce biomaterial-based drug delivery systems. However, these methods inevitably involve many complicated processes. To improve this, the inventors of the present invention applied 3D printing technology to fabricate a patch with a structure in which the inner and outer layers are spatially separated in a single step, without multiple physical steps. Reducing the process steps in this way reduces the overall fabrication time and helps maintain higher biological activity of growth factors. In addition, traditional approaches generally involve processing toxic solutions or additional processes under harsh environmental factors (e.g., pH, temperature). These processes also reduce the stability of protein-based drugs. However, the HAVEM ink produced by the inventors of the present invention has mild crosslinking conditions that do not form other chemically active substances such as radicals as intermediates during the synthesis process and do not require a catalyst, which can also contribute to maintaining the biological activity of growth factors.
[0101] A patch with spatiotemporally compartmentalized dual angiogenic factors has a significant effect on inducing cerebral angiogenesis. The inventors of the present invention investigated the efficacy of in vivo treatment using the OR-PAM system to monitor time-dependent changes in mouse cerebral cortex microvessels for 14 days. This imaging method does not require the use of labeling substances because it obtains vascular images by measuring PA waves generated by red blood cells present in the vasculature. When using the OR-PAM system, functional and integrated newly formed blood vessels can be identified in a more effective and non-invasive manner than existing vascular imaging techniques.
[0102] The SCAI patch developed by the inventors of the present invention can serve as a reliable guide for further investigation into the possibility of neovascularization in cerebral ischemic regions. In addition, the sustained release angiogenic growth factor releasing patch system developed by the inventors of the present invention can also be applied to the treatment of intractable chronic cerebral ischemic diseases such as Moyamoya disease. Moyamoya disease is a progressive obliterative arteriosclerosis characterized by the occlusion of the internal diameter artery and its branches. Treatment of Moyamoya disease patients is mainly carried out by surgical procedures (direct anastomosis method, indirect anastomosis method). However, in pediatric patients, the superficial temporal artery (STA) is too thin to directly anastomose to the middle cerebral artery, so direct anastomosis cannot be performed, and indirect vascular regeneration strategies, such as endovascular dural artery anastomosis (EDAS), are widely accepted as treatment strategies for pediatric Moyamoya disease. It is generally known that the effectiveness of this surgical method varies depending on the growth factor values and angiogenic ability of the cerebrospinal fluid. The SCAI patch created by the inventors of the present invention can show beneficial effects in promoting angiogenesis between the superficial temporal artery (STA) and the light tunica vessels after incision surgery simply by being placed near the site.
[0103] The results of this study highlight the excellent potential of spatiotemporally compartmentalized cerebral angiogenesis-inducing patches fabricated using HAVEM ink. The HAVEM ink is a 3D printing ink with a crosslink density regulated through an aza-Michael addition reaction. In this study, a decellularized extracellular matrix (dECM)-based hybrid ink with a crosslink density regulated through an aza-Michael addition reaction was synthesized, and a complex patch-shaped structure was fabricated using 3D printing technology based on the improved printability of the hybrid ink. Hybrid inks with higher crosslink density have smaller pore sizes due to more dense bonds, which can effectively reduce the release rate of growth factors. In addition, 3D printing technology can be used to fabricate physically compartmentalized structures that can control the release of growth factors loaded in the hybrid ink. Therefore, the SCAI patch fabricated in this study can effectively induce angiogenesis required for the treatment of ischemic diseases by sustained release of two types of angiogenic growth factors. The drug delivery platform in the form of a SCAI patch created in this study overcomes the problems that arise in conventional long-term drug delivery approaches. The patch formed from HAVEM ink containing vascular tissue-derived decellularized extracellular matrix (VdECM) and methacrylated hyaluronic acid (HAMA) is a material derived from the actual tissue, has soft and flexible properties, and has versatility in fabrication. When applied to patients with various acute or chronic cerebral ischemic diseases, the SCAI patch created in this study can be used as a promising alternative therapeutic agent because it can effectively induce angiogenesis.In addition, when various other types of drugs are applied to the spatiotemporally compartmentalized patch or a layer capable of carrying additional drugs is further formed, the spatiotemporally compartmentalized patch can effectively function as a drug delivery platform that must deliver drugs locally at a regulated dose, and can be used in a variety of applications such as the treatment of ischemic heart disease, diabetes, and the like, and coronavirus vaccines.
[0104] Although the present invention has been described through the above-mentioned embodiments, the present invention is not necessarily limited thereto, and various modifications can be made without departing from the scope and spirit of the present invention. Therefore, the scope of protection of the present invention should be interpreted as including all embodiments falling within the scope of the claims attached to the present invention.
Claims
1. A hybrid ink comprising an extracellular matrix having an amine group and a modified hyaluronic acid having an ethylenically unsaturated bond functional group introduced therein, An extracellular matrix-based hybrid ink for 3D printing, characterized in that the extracellular matrix and the modified hyaluronic acid are in a crosslinked state by chemical bonds formed between at least a portion of the amine groups present in the extracellular matrix and the ethylenically unsaturated bond functional groups present in the modified hyaluronic acid.
2. The extracellular matrix-based hybrid ink for 3D printing according to claim 1 , characterized in that the extracellular matrix is a vascular tissue-derived decellularized extracellular matrix.
3. The extracellular matrix-based hybrid ink for 3D printing according to claim 1 , characterized in that the ethylenically unsaturated bond functional group is selected from a vinyl group, an acrylic group, or a methacrylic group.
4. 2. The extracellular matrix-based hybrid ink for 3D printing according to claim 1, wherein the modified hyaluronic acid is selected from methacrylated hyaluronic acid or acrylated hyaluronic acid.
5. 2. The extracellular matrix-based hybrid ink for 3D printing according to claim 1, wherein a chemical bond between an amine group present in the extracellular matrix and an ethylenically unsaturated bond functional group present in the modified hyaluronic acid is formed by an aza-Michael addition reaction.
6. The extracellular matrix-based hybrid ink for 3D printing according to claim 1, wherein the weight ratio of the extracellular matrix to the modified hyaluronic acid is 1:0.01 to 1:0.
8.
7. The extracellular matrix-based hybrid ink for 3D printing according to claim 1, characterized in that the concentration of the extracellular matrix in the hybrid ink is 1-10% (w / v) and the concentration of the denatured hyaluronic acid is 0.01-8% (w / v).
8. The extracellular matrix-based hybrid ink for 3D printing according to claim 1 , further comprising a growth factor.
9. The growth factors include vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), epithermal growth factor (EGF), insulin-like growth factor (IGF), erythropoietin (EPO), fibroblast growth factor (FGF), brain-derived neurotrophic factor (BDNF), and nerve growth factor (NGF). growth factor (NGF), keratinocyte growth factor (KGF), interleukin (IL), colony-stimulating factor (CSF), angiopoietin (ANG), platelet-derived growth factor (PDGF), placental growth factor (PGF), transforming growth factor-α (TGF-α), transforming growth factor-β (transforming growth factor-β), 9. The extracellular matrix-based hybrid ink for 3D printing according to claim 8, characterized in that the ink is composed of one or more proteins selected from the group consisting of transforming growth factor-β, transforming growth factor-β, transforming growth factor-β, matrix metalloproteinase (MMP), and bone morphogenetic protein (BMP).
10. The extracellular matrix-based hybrid ink for 3D printing according to claim 8, characterized in that the concentration of growth factors in the hybrid ink is 0.001-1 g / l.
11. Providing an extracellular matrix solution having a pH of 6.5 to 7.5; and adding a modified hyaluronic acid having an ethylenically unsaturated bond functional group to the extracellular matrix solution, mixing the mixture uniformly, and then carrying out an aza-Michael addition reaction to obtain an ink in which the extracellular matrix and the modified hyaluronic acid are crosslinked.
12. The method for producing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, wherein the extracellular matrix is a vascular tissue-derived decellularized extracellular matrix.
13. The method for producing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, wherein the ethylenically unsaturated bond functional group is selected from a vinyl group, an acrylic group, or a methacrylic group.
14. 12. The method for preparing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, wherein the modified hyaluronic acid is selected from methacrylated hyaluronic acid or acrylated hyaluronic acid.
15. 12. The method for preparing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, wherein a chemical bond is formed between at least a portion of the amine groups present in the extracellular matrix and an ethylenically unsaturated bond functional group present in the modified hyaluronic acid by the aza-Michael addition reaction.
16. The method for preparing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, wherein the modified hyaluronic acid is added to the extracellular matrix solution in an amount of 1 to 80 parts by weight relative to 100 parts by weight of the extracellular matrix.
17. The method for producing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, characterized in that the concentration of the extracellular matrix in the extracellular matrix solution is 1 to 10% (w / v), and the denatured hyaluronic acid is added to the extracellular matrix solution to a concentration of 0.01 to 8% (w / v).
18. 12. The method of claim 11, wherein the aza-Michael addition reaction is carried out at a temperature of 1 to 10° C. for 2 to 24 hours.
19. The method for preparing an extracellular matrix-based hybrid ink for 3D printing according to claim 11, further comprising the step of adding and mixing a growth factor to the ink.
20. 20. The method for preparing an extracellular matrix-based hybrid ink for 3D printing according to claim 19, wherein the growth factor is added to the ink to a concentration of 0.001 to 1 g / l.
Citation Information
Patent Citations
Bio-ink composition for the three-dimensional printing and process for preparing the same
KR1020180125776A
Bioprinted, 3D scaffolds for cellular test beds and methods of use thereof
US20210324336A1